An exploratory study on the storytelling practices of parents with children studying in the UP Child Development Center - Arabe, Edward Francis M.; Quijano, Ma. Lourdes M.; Llano, Christian Jake N. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT A study was conducted to explore the storytelling practices of parents. Their book selection methods, storytelling schedules, storytelling techniques they use, and their perceived values of storytelling were described. A total of 22 qualified parent couples, who have children currently enrolled in the UP Child Development Center, participated in the study. All the respondents selected were interviewed. These respondents are parent couples who are married and who live in the same household. The data gathered from the interviews were qualified into themes with four major topics. The answers given by parents were tallied using frequency tables in order to describe common trends in these. Most parents did not follow a schedule in their storytelling. Plot, child's preference, child's abilities, characters, illustrations, and morals were the most common factors, arranged from most to least, considered in books selection. Voicing and acting are the most frequent storytelling techniques parents used followed by asking questions and technology. In the values perceived in the act of storytelling, parents considered cognitive development to be the most important reason why they do it. Other values are quality time, development of reading habit, parents like reading, facilitating sleep, alternative to gadgets, and for teaching moral.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Storytelling -- Philippines; Parents -- Philippines